THE MODERATING EFFECT OF SUSTAINABILITY REPORT ON THE RELATIONSHIP BETWEEN CAPITAL STRUCTURE, FIRM SIZE, FINANCIAL PERFORMANCE, AND GOOD CORPORATE GOVERNANCE ON FIRM VALUE - Eka Meirawati; Achmad Soediro; Nurul Izzah Az Zahra (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2023)
This study examined the effect of Capital Structure, Company Size, Financial Performance, and Good Corporate Governance on Firm Value and Sustainability Reports as moderating variables in banking sector companies listed on the Indonesia Stock Exchange in 2018-2020. It used a quantitative method with the method of moderated regression analysis (MRA). The data used in this study was secondary data with a population of all banking sector companies that publish sustainability reports and are listed on the Indonesia Stock Exchange in 2018-2020. The sampling technique in this study used a purposive sampling technique and produced a total sample of 30 companies. The results showed that the capital structure and firm size did not affect firm value. Financial Performance and Good Corporate Governance affect the Company's Value. The Sustainability Report was able to moderate the effect of Capital Structure, Company Size, and Good Corporate Governance on firm value. On the contrary, the Sustainability Report was not able to moderate the effect of Financial Performance on Firm Value.